Global, regional, and national burdens of myocarditis, 1990–2019: systematic analysis from GBD 2019 - Yue-Wen-Ying Wang; Run-Ben Liu; Cheng-Yang Huang; Hao-Yang Li; Zhi-Xin Zhang; Xiao-Zheng Li; Jia-Ling Liu; Chao Zhang; Xing Xiong; Yu-Ming Niu (BMC Public Health, 2023)
Abstract Objectives Myocarditis, a health-threatening heart disease, is attracting increasing attention. This systematic study was conducted to study the prevalence of disease through the trends of incidence, mortality, disability-adjusted life years (DALYs) over the last 30 years, which would be helpful for the policymakers to better the choices for reasonable decisions. Methods The global, regional, and national burdens of myocarditis from 1990–2019 were analyzed by using the 2019 Global Burden of Disease (GBD) database. This study on myocarditis produced new findings according to age, sex, and Social-Demographic Index (SDI) by investigating DALYs, age-standardized incidence rate (ASIR), age-standardized death rate (ASDR), and corresponding estimated annual percentage change (EAPC). Results The number of myocarditis incidence increased by 62.19%, from 780,410 cases in 1990 to 1,265,770 cases in 2019. The ASIR decreased by 4.42% (95%CI, from -0.26% to -0.21%) over the past 30 years. The number of deaths from myocarditis increased by 65.40% from 19,618 in 1990 to 324,490 in 2019, but the ASDR was relatively stable over the investigated period. ASDR increased in low-middle SDI regions (EAPC=0.48; 95%CI, 0.24 to 0.72) and decreased in low SDI regions (EAPC=-0.97; 95%CI, from -1.05 to -0.89). The age-standardized DALY rate decreased by 1.19% (95%CI, from -1.33% to -1.04%) per year. Conclusions Globally, the ASIR and DALY for myocarditis decreased and the ASDR was stable over the past 30 years. The risk of incidences and death cases increased with age. Measures should be taken to control the risk of myocarditis in high-burden regions. Medical supplies should be improved in the high-middle SDI regions and middle SDI regions to reduce the deaths from myocarditis in these regions.